Effects of NCMS Coverage on Access to Care and Financial Protection in China - Zhiyuan Hou; Ellen Van de Poel; Eddy Van Doorslaer; Baorong Yua; Qingyue Menge (Tinbergen Institute, 2012)
The introduction of the New Cooperative Medical Scheme in rural China is one of the largest health care reforms in the developing world since the millennium. The literature to date has mainly used the uneven rollout of NCMS across counties as a way of identifying its effects on access to care and financial protection. This study exploits the cross-county variation in NCMS generosity in 2006 and 2008 in Ningxia and Shandong province and adopts an instrumenting approach to estimate the effect of a continuous measure of coverage level. Our results confirm earlier findings of NCMS being effective in increasing access to care, but not increasing financial protection. In addition, we find that NCMS enrollees are sensitive to the incentives set in the NCMS design when choosing their provider, but also that providers seem to respond by increasing prices and/or providing more expensive care.
urn:NBN:nl:ui:15-1765/32659
Keywords: D63; I14; 330; Health insurance; access; financial protection; China; Basisgesundheitsversorgung; Gesundheitsreform; Gesundheitsfinanzierung; Shandong; Ningxia